Abundant Quantitative Trait Loci Exist for DNA Methylation and Gene Expression in Human Brain - Gibbs, J. Raphael; van der Brug, Marcel P.; Hernandez, Dena G.; Traynor, Bryan J.; Nalls, Michael A.; Lai, Shiao-Lin; Arepalli, Sampath; Dillman, Allissa; Rafferty, Ian P.; Troncoso, Juan; Johnson, Robert; Zielke, H. Ronald; et al. (PLoS genetics, 2010)
A fundamental challenge in the post-genome era is to understand and annotate the consequences of genetic variation, particularly within the context of human tissues. We present a set of integrated experiments that investigate the effects of common genetic variability on DNA methylation and mRNA expression in four human brain regions each from 150 individuals (600 samples total). We find an abundance of genetic cis regulation of mRNA expression and show for the first time abundant quantitative trait loci for DNA CpG methylation across the genome. We show peak enrichment for cis expression QTLs to be approximately 68,000 bp away from individual transcription start sites; however, the peak enrichment for cis CpG methylation QTLs is located much closer, only 45 bp from the CpG site in question. We observe that the largest magnitude quantitative trait loci occur across distinct brain tissues. Our analyses reveal that CpG methylation quantitative trait loci are more likely to occur for CpG sites outside of islands. Lastly, we show that while we can observe individual QTLs that appear to affect both the level of a transcript and a physically close CpG methylation site, these are quite rare. We believe these data, which we have made publicly available, will provide a critical step toward understanding the biological effects of genetic variation.